Pengaruh Sistem Pengelolaan Dana Kelurahan Dan Sistem Informasi Pengelolaan Keuangan Daerah Terhadap Kualitas Laporan Keuangan Dimediasi Akuntabilitas - Reza Cahya Anggraini; Saiful Anwar (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to find out, test and prove the effect of village fund management and regional financial management information systems on the quality of financial reports with accountability. The research method used is quantitative method and uses primary data by distributing questionnaires. The research sample used the Slovin Formula and had a population of 104 respondents, namely village officials from 3 subdistricts in Surabaya, namely Sambikerep Subdistrict, Tandes Subdistrict and Pakal Subdistrict, so that the sample of this study was 70 respondents. The data analysis technique used in this research uses Partial Least Square (PLS). The results of this study indicate that the Village Fund Management shows no significant results on the Quality of Financial Reports, the Regional Financial Management Information System shows that it has no significant effect on the quality of financial reports, the regional financial management information system shows a significant influence on accountability, and accountability has a significant effect on the quality of financial reports. Keywords: Urban Village Fund Management, Regional Financial Management Information System, Quality of Financial Statements and Accountability